EFISIENSI SISTEM E-PROCUREMENT DALAM PELELANGAN UMUM PENGADAAN BARANG DAN JASA (STUDI KASUS: DINAS PEKERJAAN UMUM PROVINSI BALI) - Claudy, Fransiskus; Noak, Piers Andreas; Winaya, I Ketut (CITIZEN CHARTER, 2017)
ABSTRACT E-procurement system in the procurement of government goods / services is essential to improve the efficiency of the procurement process, this is the purpose and principles of procurement process government goods / services, including the Public Works Department of Bali Province as one SKPD Bali Province who have used the e-procurement system in the procurement process. The purpose of this study was to determine the efficiency as well as the constraints of e-procurement system in the procurement of government goods / services performed particularly of Public Works Department of Bali Province. This type of research is using descriptive qualitative approach. Source data used are primary data and secondary data. The results of the analysis of the findings and conclusions of research are e-procurement system in the procurement of goods / services conducted by the Public Works Department of Bali Province has been run in full and more efficient than the conventional way. This is evidenced by the results of the field survey and data procurement conducted by the Public Works Department of Bali Province in particular prone years. But it need to increase the use of electronic systems in other procurement methods, as well as the development of the server to operate the system that are not easily hacked or suffer other server error, given the e-procurement system based online. So that in the future, e-procurement system will be more efficient and transparent in accordance with the principles and objectives. Â Keywords: E-procurement, procurement of goods / services, efficiency